PERBANDINGAN METODE EKSTRAKSI MASERASI DAN SOKHLETASI TERHADAP KADAR FLAVONOID TOTAL EKSTRAK ETANOL 96% DAUN KLUWIH (Artocarpus camansi) - M. Hidayatullah; Eka Fitri Susiani; Regita Wananda Putri Gita (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
The utilization of medicinal plants is one of the steps for alternative medicine. One of them is the kluwih plant (Artocarpus camansi) which is also similar to the breadfruit plant but has differences in its fruit. The purpose of this research is to analyze the total flavonoid content of 96% ethanol extract of kluwih leaves and which method has the potential to produce greater total flavonoid content. Extraction of kluwih leaves was done by maceration and sokhletation. The method implemented was UV-Vis spectrophotometry with AlCl3 reagent and involving quercetin as a comparator. Based on the analysis by applying the maceration method, an average level of 23.05 mg QE/g extract was obtained for the total flavonoid content of 96% ethanol extract of kluwih leaves, while the sokhletation method obtained an average of 31.33 mg QE/g extract. So it can be concluded that the extraction method that produces a greater total flavonoid content of 96% ethanol extract of kluwih leaves is sokhletasi.